A Note on the Ogham Inscription from Buckquoy, Orkney. (1st January 2017) - Rodway, Simon
I tentatively propose a new Gaelic interpretation of an ogham inscription on a spindle-whorl from Buckquoy in Orkney. In this interpretation, the spindle-whorl would be a gift from a man to a female spinster.